Stress-resilient maize hybrids with stable agronomic performance: a pursuit to strengthen sustainable maize production in India - Kumar, Ramesh; Kondajji, Yathish Rangappa; Das, Abhijit Kumar; Kumar, Sushil; Kaur, Yashmeet; Kumar, Kamlesh; S., Jayasudha; Karjagi, Chikkappa Gangadhar; Patel, Manish B.; Karad, Sunil; Jat, B. S.; Zaidi, Pervez H.; et al. (Frontiers in Plant Science, 2025)
Genotype by environment (G×E) interactions are of great interest for breeders to identify test locations and adapted genotypes. In the present study, 20 sub-tropical maize hybrids along with 5 commercial checks were planted at different locations under different ecologies (drought, high temperature, water logging and optimum environments) and evaluated for grain yield through the Best Linear Unbiased Estimations (BLUEs) and the Best Linear Unbiased Predictors (BLUPs). Genotypic and phenotypic correlations were also obtained among the different locations within the diverse ecologies. The trials were conducted during winter 2023 under drought, Spring 2024 under high temperature stress and under water logging during rainy 2023, respectively. The Genotype main effect plus genotype x environment interaction (GGE) biplot indicated that first and second principal components (PC1 and PC2) explained 100% of variation in drought, heat stress, water logging conditions. Under optimal conditions, it explained 75.81% variation. As per BLUE and BLUP, DKC 9144 and BH 417177 under drought, RCRMH 20 was under heat stress and BH 417144 under waterlogging were the best. Dendrogram was generated using Ward’s method of cluster analysis. Genotype RCRMH 20 was identified as the best performing genotype under heat (at locations Begusarai, Godhra and Kolhapur) and at water logging (Ludhiana, Hyderabad and Varanasi) with mean yield of 60.07 q/ha and 50.52 q/ha respectively. Based on these results it is recommended that hybrids namely MFH 2265, BH 417144, RCRMH 20 and BH 417177 may be tested in larger plot size before recommendation for release for commercial cultivation based on their performance in respective zones.